Seleção de genótipos de milho e respostas fisiológicas ao déficit hídrico em região semiárida - Santos, Jacilene Francisca Souza (2023)
Drought tolerance in maize cultivation is a multifactorial and intricate trait, involving a multitude of adaptive mechanisms and diverse plant responses to water stress. The study aimed to assess the physiological response to drought tolerance and the combining ability among different genetic classes of maize under water deficit during the juvenile phase under water deficit conditions. Additionally, it aimed to identify prospective parental lines for establishing a foundational breeding population in the semiarid region The trials were conducted in both greenhouse and rainfed conditions, established within the experimental area of Embrapa Semiarid, located in Nossa Senhora da Glória, SE. To achieve this, a total of 60 treatments were employed, comprising 45 progenies, 10 parental hybrids, and 5 control varieties. The data obtained were subjected to analysis of variance, followed by an assessment of general combining ability (GCA) and specific combining ability (SCA). The experimental design employed in all trials was a randomized complete block design (RCBD). For the greenhouse experiment, there were three replications with three plants per plot, while for the rainfed experiment, there were two replications with two rows per plot. The variables analyzed encompassed relative water content (RWC), electrolyte leakage (EL), plant and ear heights, male and female flowering, grain weight and grain yield. In the juvenile phase, there was a significant effect of GCA and SCA for the variables RWC (relative water content) and EL (electrolyte leakage), indicating the importance of both additive and non-additive genetic effects in regulating the physiological expression of plants under water deficit conditions. Furthermore, the SCA effect was predominant over GCA, highlighting the dominance of nonadditive gene effects. In the rainfed experiment, the predominance of GCA over SCA revealed the prevalence of additive gene effects. The mean squares of GCA were significant for all variables, including plant height (PH), ear height (EH), male flowering (FM), female flowering (FF), and grain yield (PG). These results indicate that additive genetic effects are important in controlling the expression of these traits in plants under rainfed conditions. Based on the analyzed traits, it can be observed that parents P1, P2, P4, and P7 showed superiority in forming populations with greater tolerance to water deficit during the juvenile phase. This is evident from their high and positive values of GCA. In the rainfed environment, among the parental lines utilized, P2 POPOTOL2 demonstrates beneficial traits. The analyzed variables indicate that POPOTOL2 exhibits genetic variability that can be harnessed for the formation of a base breeding population with substantial genetic potential, particularly suitable for utilization in the semiarid region. Thus, the successful selection of new drought-tolerant genotypes through population improvement is evident, enabling the identification of drought-tolerant maize genotypes at the juvenile stage. This selection provides an alternative for the development of a new population in the semiarid region.